The new planning for results : - Nelson, Sandra S. (American Library Association, 2001)
Design a planning process customized to your setting with the help of Nelson's do's and dont's, in-depth reports of Anytown Library's experience with the process, and reproducible workforms. allocate resources based on current and future needs.